IMPROVING STUDENTS' VOCABULARY BY USING JOOX APPLICATION - Aulia Hanifah Qomar; Fenny Theresia; Vina Pandu Dermayanti (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The purpose of this study is to improve students’ vocabulary by using JOOX application. In the Pre-Test result, the students who got score ≥ 13 were 21.88%, otherwise 79.12% were under achievement students. Then, the students who got score ≥ 13 in Post-Test 1 were 81.25% while 19.75% student got score < 13. Furthermore, in Post-Test 2 result all the students (100%) got score ≥ 13. The use of the JOOX application media in teaching and learning process can improve the students’ activity in the classroom, the students’ activities in cycle 1 were categorize into fair category. The students’ activities was 66% (get score 33 of the 50 maximal score). Then, in cycle 2 it could be seen that the students’ activities were categorize into good category. The students’ activities was 80% (get score 40 of the 50 maximal score). It is indicated that the students’ vocabulary mastery could improve significantly after the treatment applied in the teaching and learning process.